GCT-76. 24Gy WHOLE VENTRICULAR RADIOTHERAPY ALONE IS SUFFICIENT FOR DISEASE CONTROL IN LOCALISED GERMINOMA IN CR AFTER INITIAL CHEMOTHERAPY – EARLY RESULTS OF THE SIOP CNS GCT II STUDY. (4th December 2020) - Calaminus, Gabriele; Bison, Brigitte; Faure-Conter, Cecile; Frappaz, Didier; Peyrl, Andreas; Gerber, Nicolas; Müller, Jans-Enno; Thankamma, Ajithkumar; Mitra, Dipayan; Cross, Justin; Pietsch, Torsten; Smith, Colin; et al.
Abstract: SIOP CNS GCT II aimed to establish if 24Gy Whole Ventricular Radiotherapy (WVRT) in localised germinoma is sufficient for tumour control. After central review of radiological response after 'CarboPEI' chemotherapy, patients in complete remission (CR) were consolidated with 24Gy WVRT. Between 2/2012 and 7/2018, 182 patients from 8 European countries with histologically-confirmed fully-staged localised germinoma were registered. 70 patients were in CR after chemotherapy, 98 in partial remission (PR), seven had stable disease, two progressive disease, and in five no response data were documented. Of the 70 patients in CR, 58 received 24Gy WVRT alone; two of these relapsed, one local and one disseminated, two and six years after diagnosis. Of the 98 patients in PR after chemotherapy, 86 received 24Gy WVRT and 16Gy boost, of which five relapsed (three local, two distant) 12–24 months from diagnosis. Twelve patients in each of the CR/PR groups received non-protocol or undocumented radiotherapy fields/doses. Median follow-up was 3.7 years. Event-free survival (EFS) for patients in CR and with WVRT only (n=58) was 98% at 4 years. 4-years EFS of patients with PR and WVRT 24Gy and 16Gy tumor boost (n=86) was 95%. Localised germinoma in CR after chemotherapy had an excellent outcome with 24Gy WVRT alone; 24GY WVRT can therefore be considered standard consolidation treatment in this group. International consensus on radiological response criteria is of utmost importance to avoid over- and undertreatment of such patients and to pave the way for further treatment reduction in this group of patients.